The process of sustainability reporting in international hotel groups: an analysis of stakeholder inclusiveness, materiality and responsiveness (2018)
While extensive research covers the disclosure of performance in sustainability reports, there is limited understanding of the process of how such reports are developed and whose priorities they reflect. We investigate the sustainability reporting, focusing on stakeholder-related practices disclosed by the 50 largest hotel groups worldwide, by testing the AA1000 Stakeholder Engagement Standard. We use the three interrelated dimensions (inclusiveness, materiality and responsiveness) to assess the disclosure of how organisations (1) identify and engage with stakeholders, (2) determine the importance of sustainability issues, and (3) respond to stakeholder concerns. We find the low transparency and imprecision of decision-making criteria and processes suggest sustainability reporting is more of a legitimisation exercise than one of accountability. We find the stakeholder identification approach does not inform the organisation's transparency, whereas the dialogue mechanisms used to empower stakeholders, as their participatory role in decision-making and the reporting process, shape the disclosure of materiality and responsiveness. We demonstrate how that the ability to determine stakeholder engagement, materiality analysis and responsiveness of the sustainability reporting process can improve the role of sustainability reports as a mechanism for accountability, and we argue the importance of the alignment between the degree of disclosure on inclusiveness, materiality and responsiveness. © 2017, © 2017 Informa UK Limited, trading as Taylor and Francis Group.